Poetry as Salve for Persian Exiles - Seyed-Gohrab, Asghar (My University, 2021)
With the coming of the 1979 Revolution and the Iran–Iraq War (1980–88), Persian poetry entered into a new phase. While the revolutionary poets wrote about the ideals of the revolution, motivating young soldiers to go to the front, many established poets were persecuted, imprisoned, or executed, and some chose exile. From this period onward, a rich corpus of Persian poetry about exile has been created. With minds in their new homes and hearts in the homeland, the poets reflect on a wide range of new experiences. What strikes me in reading the poetry of exiled Iranians is that their poetry, as well as their other writings, usually starts with traumatic experiences in prisons before and after the revolution, followed by reflective narratives about their flight from Iran, and a period of adaptation and even acceptance of the new culture, elaborating on life in exile with all its hardships and problems. In these three phases, poetry often functions as a salve, offering poets a space for reflection and contemplation. The authors have recourse to classical Persian poetry, which conveys the ephemerality of life, to universalize the theme of exile by relating it to a mystical longing of the soul for its original abode and to the uncertainties of mundane life. While classical poetry is restorative for pains and tribulations, the exiled authors also compose their own poetry depicting a bitter and souring process of acquiescence to an uncertain life in the diaspora. In this essay, I will first give an example of how classical Persian poetry is used by the diaspora in an exilic context, and then, I will analyze the poetry of three Persian poets: Nasim Khaksar, Pegah Ahmadi, and Fatemeh Shams. There are a large number of Persian poets in the diaspora whose poetry deserves to be analyzed. Each of these poets, whether they are established, amateur, or novice, reveals a new aspect of life in exile.
Keywords: Taverne